Informal financial education and consumer financial capability: The mediating role of financial knowledge - Chen, Fuzhong; Lu, Xiuli; Wang, Wenting (Frontiers in Psychology, 2022)
With the development of the economy, family wealth continues to accumulate, and more and more consumers participate in financial management affairs. As an important way to improve financial knowledge, informal financial education is vital to consumer financial capability. Utilizing data from the 2012, 2015, and 2018 US National Financial Capability Study (NFCS) and the approaches of ordinary least squares (OLS) and ordered probit regression are employed to produce more accurate estimates. Meanwhile, the study also explores the mediating effects of financial knowledge between informal financial education and consumer financial capability. The results show that informal financial education has a positive effect on the improvement of consumer financial capability. Besides, financial knowledge partially mediates the nexus between informal financial education and consumer financial capability. Therefore, policymakers are encouraged to formulate measures to promote financial education programs not only in schools and universities but also in workplaces or communities. Companies also should offer more opportunities for their employees to receive financial education and further enhance their financial capability. Consumers should be aware of the importance of financial education and actively learn financial knowledge to improve financial capability and further enhance financial satisfaction.